Complete larval development of the Brachyuran crab (Epixanthus Frontalis H. Milne Edwards, 1834) (Crustacea, Decapoda, Eriphioidea, Oziidae) under laboratory conditions - Al-Aidaroos, Ali M.; Al-Haj, Ahmed E.; Kumar, A. A.j. (Zootaxa, 2014)
The complete larval development of the oziid crab Epixanthus frontalis (H. Milne Edwards, 1834) hatched from ovigerous specimens collected from Saso Island, southern Red Sea, was obtained under laboratory conditions. Four zoeae, one additional zoea and a megalopa were obtained and these are described and illustrated in detail for the first time. Larvae of this species can be differentiated from those of other oziid species based on a combination of characters such as the number of aesthetascs and setae of the antennule, and the coxal and basial setal numbers and patterns of the maxilla and maxillule.